Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1016/s0002-9440(10)61211-4
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer T (NKT) Cells Attenuate Bleomycin-Induced Pulmonary Fibrosis by Producing Interferon-γ

Abstract: Pulmonary fibrosis is a progressive illness characterized by interstitial fibrosis. Although the precise mechanism for pulmonary fibrosis is not completely understood, an immune response involving interferon (IFN)-gamma appears to play a role. Therefore, we examined the functional roles of natural killer T (NKT) cells, which produce IFN-gamma and interleukin-4 on activation, in bleomycin-induced pulmonary fibrosis. In NKT cell-deficient mice, pulmonary fibrosis was worse in terms of histology, hydroxyproline l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
61
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 46 publications
5
61
1
Order By: Relevance
“…34 In line with the current studies, there is growing literature that certain subsets of T cells are beneficial because mice with severe combined immunodeficiency developed more severe fibrosis in response to asbestos, which was reduced on reconstitution with T cells. 11 Furthermore, use of mice deficient in natural killer T cells 35 or ␥␦ T cells 36 has shown worsened fibrosis, suggesting that specific subsets of T cells are responsible for regulating fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…34 In line with the current studies, there is growing literature that certain subsets of T cells are beneficial because mice with severe combined immunodeficiency developed more severe fibrosis in response to asbestos, which was reduced on reconstitution with T cells. 11 Furthermore, use of mice deficient in natural killer T cells 35 or ␥␦ T cells 36 has shown worsened fibrosis, suggesting that specific subsets of T cells are responsible for regulating fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Therefore, NKT cells regulate various immune responses related to autoimmune diseases, hypersensitivity pneumonia, pulmonary fibrosis, oral tolerance, transplantation rejection, and graftversus-host disease. 1,[4][5][6][7][8][9][10] In addition, they enhance the immune response to tumors, microorganisms, and inflammation. 4,11,12 The results of a recent phase I clinical trial using Va24 NKT cells activated by a-galactosyl ceramide (a-GalCer) in patients with advanced and recurrent nonsmall-cell cancer 13 suggested that activating reagents for NKT cells may be good candidates for regulating immune disease.…”
mentioning
confidence: 99%
“…NKT cells play critical roles in various immune responses in vivo, e.g., in the maintenance of self-tolerance, in autoimmune diseases (2)(3)(4), in tumor rejection (5), in pulmonary fibrosis (6), and in response to various infectious agents (7)(8)(9). Upon activation, NKT cells rapidly produce large amounts of IL-4 and IFN-␥ (10), which play critical roles in the regulation of innate and adaptive immune responses (1).…”
mentioning
confidence: 99%